PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE WORD SQUARE DENGAN STRATEGI CROSSWORD PUZZLE TERHADAP PRESTASI BELAJAR IPS SISWA KELAS VIII SMP NEGERI 8 BANDA ACEH - Eva Linda; Teuku Abdullah; Nurasiah . (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2018)
ABSTRACTThe research entitled "The Influence of Cooperative Learning Model of Word Square Type with Crossword Puzzle Strategy on Student Achievement of IPS Grade VIII of SMP Negeri 8 Banda Aceh" is aimed to analyze the influence of cooperative learning model of Word Square type with Crossword Puzzle strategy on IPS student achievement in grade VIII SMP Negeri 8 Banda Aceh. The approach that use in this research are a quantitative and the type of the is experimental research. The population in this research is all students of class VIII SMP Negeri 8 Banda Aceh which amounts to 143 students and consists of 7 classes. The sample is the students of class VIII.2 as the experimental class and the students of class VIII.1 as the control class consisting of 22 students each. The technique of collecting the data are tests and documentation. The technique of analysisthe data in this research is (1) calculate the mean value; (2) calculate the variance and standard deviation; (3) normality test; (4) homogeneity test of variance; and (5) t-test. Based on the technique of data analysis, the average value of the experimental class is 79.8 and the control class is 72.7. The variance and standard deviation of the experimental class were 80.52 and 8.97 while the control classes were 45.94 and 6.78. The experimental class normality test is 3.57 and the control class is 0.96. The homogeneity test of experimental class variance and control class was 1.75. And the t-test result is 3.19. Based on the data analysis above, it can be concluded that the average value of eskperimen class is higher than control class. The data distribution of the final test score of the students in the experimental class and the control class is normally distributed based on the significant level of x2countx2tablethat is 3.57 7.81 and 0.96 7.81. To test the homogeneity of variance is Fcount≤ Ftable is 1.75 ≤ 2.09, then the variance of experimental class data and control class is homogeneous. Results of data processing using t-test analysis obtained tcount = 3.19 while ttable = 2.02. Means that tcountttable is 3.19 2.02, thus according to the testing criteria then H0 is rejected and Haisaccepted. Keyword: crossword puzzle, cooperative learning,learning achievement, word square. ABSTRAKPenelitian yang berjudul “Pengaruh Model Pembelajaran Kooperatif Tipe Word Square dengan Strategi Crossword Puzzle terhadap Prestasi Belajar IPS Siswa Kelas VIII SMP Negeri 8 Banda Aceh” ini bertujuan untuk menganalisis pengaruh model pembelajaran kooperatif tipe Word Square dengan strategi Crossword Puzzle terhadap prestasi belajar IPS siswa kelas VIII SMP Negeri 8 Banda Aceh. Penelitian ini menggunakan pendekatan kuantitatif dan jenis penelitian eksperimen. Populasi dalam penelitian ini adalah seluruh siswa kelas VIII SMP Negeri 8 Banda Aceh yang berjumlah 143 siswa dan terdiri dari 7 kelas. Sampelnya adalah siswa kelas VIII.2sebagai kelas eksperimen dan siswa kelas VIII.1sebagai kelas kontrol yang masing-masing terdiri dari 22 siswa. Teknik pengumpulan data dalam penelitian ini yaitu menggunakan test dan dokumentasi. Teknik analisis data dalam penelitian ini adalah (1) menghitung nilai rata-rata; (2) menghitung varians dan simpangan baku; (3) uji normalitas; (4) uji homogenitas varians; dan (5) uji-t. Berdasarkan teknik analisis data tersebut maka diperoleh nilai rata-rata kelas eksperimen adalah 79,8 dan kelas kontrol adalah 72,7. Varians dan simpangan baku kelas eksperimen adalah 80,52 dan 8,97 sedangkan kelas kontrol adalah 45,94 dan 6,78. Uji normalitas kelas eksperimen adalah 3,57 dan kelas kontrol adalah 0,96. Uji homogenitas varians kelas eksperimen dan kelas kontrol adalah 1,75. Dan hasil uji-t adalah 3,19. Berdasarkan hasil analisis data di atas, dapat disimpulkan bahwa nilai rata-rata kelas eskperimen lebih tinggi dari kelas kontrol. Sebaran data nilai tes akhir siswa pada kelas eksperimen dan kelas kontrol berdistribusi normal berdasarkan taraf signifikan x2hitung x2tabel yaitu 3,57 7,81 dan 0,96 7,81. Untuk uji homogenitas varians yaitu Fhitung ≤ Ftabel yaitu 1,75 ≤ 2,09, maka varians data kelas eksperimen dan kelas kontrol adalah homogen. Hasil pengolahan data menggunakan analisis uji-t diperoleh thitung = 3,19 sedangkan ttabel = 2,02. Berarti bahwa thitung ttabel yaitu 3,19 2,02, dengan demikian sesuai dengan kriteria pengujian maka H0 ditolak dan Ha diterima.Kata Kunci: crossword puzzle, pembelajaran kooperatif, prestasi belajar, word square.